2020
DOI: 10.1029/2019gl086372
|View full text |Cite
|
Sign up to set email alerts
|

Flux Erosion of Magnetic Clouds by Reconnection With the Sun's Open Flux

Abstract: Magnetic clouds (MCs) are flux rope magnetic structures forming a subset of solar coronal mass ejections, which have significant space weather impacts. The geoeffectiveness of MCs depends on their properties, which evolve during their interplanetary passage. Based on an analysis of observations spanning two solar cycles, we establish that MCs interacting with the ambient solar wind magnetic field (i.e., heliospheric open flux) lose a substantial amount of their initial magnetic flux via magnetic reconnection, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…During interplanetary propagation, FRs can interact and reconnect with the ambient interplanetary magnetic field. Reconnection of FR field lines can lead to substantial erosion of FR flux in the azimuthal plane (i.e., the plane formed by the FR axis and spacecraft trajectory in the FR frame), and therefore to the imbalance of the azimuthal flux (Ruffenach et al 2012(Ruffenach et al , 2015Pal et al 2020). In contrast, if no erosion occurs during interplanetary propagation and flux is conserved in the FR azimuthal plane, the MC azimuthal flux measured at 1 AU in situ ideally should be equal to the initial FR flux.…”
Section: Determination Of Fr Azimuthal Fluxmentioning
confidence: 99%
See 3 more Smart Citations
“…During interplanetary propagation, FRs can interact and reconnect with the ambient interplanetary magnetic field. Reconnection of FR field lines can lead to substantial erosion of FR flux in the azimuthal plane (i.e., the plane formed by the FR axis and spacecraft trajectory in the FR frame), and therefore to the imbalance of the azimuthal flux (Ruffenach et al 2012(Ruffenach et al , 2015Pal et al 2020). In contrast, if no erosion occurs during interplanetary propagation and flux is conserved in the FR azimuthal plane, the MC azimuthal flux measured at 1 AU in situ ideally should be equal to the initial FR flux.…”
Section: Determination Of Fr Azimuthal Fluxmentioning
confidence: 99%
“…It is evident from Dasso et al (2006) that erosion may remove flux and helicity from FRs and result in asymmetry in the FR azimuthal flux. Pal et al (2020) further showed that FR erosion is modulated by the solar cycle and may affect the geoeffectiveness of FRs.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A poloidal dipolar field, on the other hand, is created by the shift of energy from the toroidal field to the poloidal field due to the dispersion and decay of the BMRs via surface flux transport processes during the declining phase of the solar cycle (Babcock, 1961;Bhowmik & Nandy, 2018;Leighton, 1969). The largescale solar magnetic field that is tied to the solar activity cycles as described above governs the coronal conditions and plays a role in balancing the heliospheric open flux and the resulting HMF (see e.g., Pal et al, 2020;Schwadron et al, 2010).Many attempts have been made to understand the cause of the longer-term solar variations. These variations dictate the amplitude of the solar cycles (…”
mentioning
confidence: 99%